Android Studio Koala Essentials - Java Edition: Developing Android Apps Using Android Studio Koala Feature Drop and Java - Smyth, Neil (Payload Media, 2023)
This book, fully updated for Android Studio Koala Feature Drop (2024.1.2) and the new UI, teaches you how to develop Android-based applications using the Java programming language.